2006
DOI: 10.1007/s00540-006-0390-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humidifying devices on the measurement of tidal volume by mechanical ventilators

Abstract: Monitored expiratory tidal volume was underestimated by approximately 10%, when using a heat-moisture exchanger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…3,4 In some cases, suboptimal pressure support levels may be insufficient to overcome the humidifier's internal resistance and, hence, may lead indirectly to a slower decrease in PaCO 2 , as shown in the current study. 2 Such effect will be of greater relevance in patients with higher degrees of expiratory air flow obstruction and acidosis.…”
Section: Hme Internal Resistance and Performancementioning
confidence: 75%
See 2 more Smart Citations
“…3,4 In some cases, suboptimal pressure support levels may be insufficient to overcome the humidifier's internal resistance and, hence, may lead indirectly to a slower decrease in PaCO 2 , as shown in the current study. 2 Such effect will be of greater relevance in patients with higher degrees of expiratory air flow obstruction and acidosis.…”
Section: Hme Internal Resistance and Performancementioning
confidence: 75%
“…Fujita et al showed that monitored expiratory tidal volume was underestimated with different ventilators from 8% to 14% when using an HME. 4 Thus, the difference we found in minute ventilation (15.5 Ϯ 6.4 L/min with HME vs 13.7 Ϯ 5.8 L/min with HH, P Ͻ .001) may have been even larger if one considers a potential overestimation of volumes with HH.…”
Section: The Authors Respondmentioning
confidence: 77%
See 1 more Smart Citation
“…Theoretically, warm and humid air has a larger volume expansion that requires an additional correction. 17 …”
mentioning
confidence: 97%
“…This is crucial point during prolonged mechanical ventilation[5] and monitoring ventilatory parameters. [6]…”
mentioning
confidence: 99%